The Electronic Book in the University Environment: Problems for its Adoption - Domínguez Hernández, José Antonio; Ruiz-Velasco Sánchez, Enrique; Bárcenas López, Josefina; Tolosa Sánchez, José Santos; Reyes García, Amairani Ixchel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
The integration of electronic books as elements destined to favor the construction of learning in educational processes, supposes a series of previous knowledge concerning the hypertext tendencies of the e-book that the university students should have, given the characteristics of the current society in the that young people make daily use of this type of technology to carry out various tasks. In this tenor, the present work accounts for an investigation carried out with a student population of the Dentist Surgeon Career, whose objective was to identify those elements involved with the adoption of the book in electronic format as a didactic support for the subject Methodology of the Investigation.